Adsorption of an Amphoteric Aromatic Compound (-Aminobenzoic Acid) onto Different Polymeric Adsorbents - Hai-Ling Wang; Jin-Long Chen; Quan-Xing Zhang (Adsorption Science & Technology)
The adsorptive properties of p -aminobenzoic acid onto macroporous, hypercrosslinked and multi-functional polymeric adsorbents were investigated systematically in the present study in relation to the particular physicochemical characteristics of an aromatic amphoteric compound containing both Lewis acid and Lewis base functional groups. A comparison of the thermodynamic and kinetic behaviours of the adsorbate towards three different polymeric adsorbents was made. It was found that the equilibrium adsorption data for the three polymeric adsorbents were well fitted by the empirical Freundlich isotherm. The results showed that the adsorption capacity of the multi-functional polymeric adsorbent NJ-99 was the largest among the three adsorbents studied. This may be attributed to strong hydrogen-bonding interaction and electrostatic interaction between the amino groups on the resin and the carboxyl group of p -aminobenzoic acid. In contrast, because of its smaller micropore volume, the adsorption capacity of macroporous XAD-4 was lower than that of the hypercrosslinked adsorbents CHA-111 and NJ-99. Calculation of the sorption enthalpy changes enabled the adsorption mechanism to be interpreted. In addition, a kinetic study of the sorption of p -aminobenzoic acid onto NJ-99 was also undertaken. The results showed that the adsorption process was mainly controlled by intraparticle diffusion.